2019
DOI: 10.1001/jamacardio.2019.0751
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-Visit Blood Pressure Variability, Coronary Atheroma Progression, and Clinical Outcomes

Abstract: Visit-to-visit blood pressure variability (BPV) is associated with cardiovascular events, but mechanisms and therapeutic implications underlying this association are not well understood. OBJECTIVE To examine the association of intraindividual BPV, coronary atheroma progression, and clinical outcomes using serial intravascular ultrasonography. DESIGN, SETTING, AND PARTICIPANTS Post hoc patient-level analysis of 7 randomized clinical trials conducted from 2004 to 2016 involving 3912 patients in multicenter, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 31 publications
3
48
0
1
Order By: Relevance
“…4 Contrary to previous notions about visitto-visit BPV as a random phenomenon, it is highly reproducible in clinical practice and has been known to have prognostic values for a wide range of health outcomes (eg, coronary heart disease, stroke, and all-cause mortality). [5][6][7] Previous work revealed that visit-to-visit variability in systolic BP improved 8-year predictions of major CVDrelated health outcomes beyond those obtained from traditional risk factors. 8 Sleep also plays an essential role in cardiovascular health.…”
Section: Introductionmentioning
confidence: 99%
“…4 Contrary to previous notions about visitto-visit BPV as a random phenomenon, it is highly reproducible in clinical practice and has been known to have prognostic values for a wide range of health outcomes (eg, coronary heart disease, stroke, and all-cause mortality). [5][6][7] Previous work revealed that visit-to-visit variability in systolic BP improved 8-year predictions of major CVDrelated health outcomes beyond those obtained from traditional risk factors. 8 Sleep also plays an essential role in cardiovascular health.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple previous studies have demonstrated VVV, and its prognostic significance, using clinical trial data and data from longitudinal cohort studies. 7,9,11,14,15 For example, by conducting secondary analysis of the data from the ALLHAT trial, Muntner et al showed large variation in the degree of VVV across all measurements among study participants and that higher VVV of SBP was associated with increased risk of cardiovascular disease and mortality. 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses exist to explain the association between BP variability and increased cardiovascular risk. As a biologic basis, coronary atheroma progression as measured by serial intravascular ultrasonography was significantly associated with higher BP variability in a study by Clark et al 31 Other proposed mechanisms include increased wall stress, baroreceptor dysfunction, and endothelial dysfunction in those with variable BPs. Lastly, BP variability may also be a marker for medication non-compliance and may suggest that patients spend a greater proportion of time above their guideline-recommended BP goal.…”
Section: Blood Pressurementioning
confidence: 95%